Repeated intermittent administration of (R)-ketamine during juvenile and adolescent stages prevents schizophrenia-relevant phenotypes in adult offspring after maternal immune activation: a role of TrkB signaling - Tan, Yunfei; Fujita, Yuko; Pu, Yaoyu; Chang, Lijia; Qu, Youge; Wang, Xinming; Hashimoto, Kenji (European archives of psychiatry and clinical neuroscience, 2022)
Maternal immune activation (MIA) plays a role in the etiology of schizophrenia. MIA by prenatal exposure of polyinosinic:polycytidylic acid [poly(I:C)] in rodents caused behavioral and neurobiological changes relevant to schizophrenia in adult offspring. We investigated whether the novel antidepressant ( R )-ketamine could prevent the development of psychosis-like phenotypes in adult offspring after MIA. We examined the effects of ( R )-ketamine (10 mg/kg/day, twice weekly for 4 weeks) during juvenile and adolescent stages (P28–P56) on the development of cognitive deficits, loss of parvalbumin (PV)-immunoreactivity in the medial prefrontal cortex (mPFC), and decreased dendritic spine density in the mPFC and hippocampus from adult offspring after prenatal poly(I:C) exposure. Furthermore, we examined the role of TrkB in the prophylactic effects of ( R )-ketamine. Repeated intermittent administration of ( R )-ketamine during juvenile and adolescent stages significantly blocked the development of cognitive deficits, reduced PV-immunoreactivity in the prelimbic (PrL) of mPFC, and decreased dendritic spine density in the PrL of mPFC, CA3 and dentate gyrus of the hippocampus from adult offspring after prenatal poly(I:C) exposure. Furthermore, pretreatment with ANA-12 (TrkB antagonist: twice weekly for 4 weeks) significantly blocked the beneficial effects of ( R )-ketamine on cognitive deficits of adult offspring after prenatal poly(I:C) exposure. These data suggest that repeated intermittent administration of ( R )-ketamine during juvenile and adolescent stages could prevent the development of psychosis in adult offspring after MIA. Therefore, ( R )-ketamine would be a potential prophylactic drug for young subjects with high-risk for psychosis.